Tumor Necrosis Factor-Alpha’s Role in the Pathophysiology of Colon Cancer - Saleha Khan; Yara Aldawood; Ayesha Hanin Shaikh; Aleena Zobairi; Urwa Nabilah; H. M. Alqahtani; Mansoor-Ali Vaali-Mohammed (Diseases, 2025)
Colon cancer remains a significant global health challenge, with inflammatory pathways such as TNF-α playing a central role in its progression. TNF-α, a key proinflammatory cytokine, is implicated in various stages of colon cancer development, including inflammation, tumor growth, and metastasis. This review provides a comprehensive overview of the molecular mechanisms through which TNF-α contributes to colon cancer progression, with a focus on its interaction with signaling pathways like NF-κB and the Wnt/β-catenin in humans. TNF-α’s involvement in promoting tumorigenesis and its complex role in the tumor microenvironment highlight its potential as both a therapeutic target and a challenge for effective treatment. This review explores the potential of anti-TNF-α therapies and the emerging role of combination strategies with immune checkpoint inhibitors. Despite promising preclinical findings, clinical application faces challenges due to the dual role of TNF-α in both promoting and inhibiting tumor progression. Future research should aim to overcome resistance mechanisms, develop personalized therapeutic strategies, and balance the effects of TNF-α in cancer therapy.